2019
DOI: 10.1002/qj.3614
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of turbulence parametrizations in convective clouds and their environment based on a large‐eddy simulation

Abstract: The representation of deep convective clouds by convection‐permitting models could be improved by parametrizing the subgrid turbulent fluxes better. Following the work of Verrelle et al., a large‐eddy simulation (LES) of a population of convective clouds at 50‐m grid spacing was explored during the cloud life cycle to characterize the second‐order moment turbulent fluxes. The reference turbulence fields were deduced by coarse‐graining the LES outputs at horizontal grid resolutions of 500 m and 1 and 2 km. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
(102 reference statements)
1
15
0
Order By: Relevance
“…The eddies near the cloud edges, which are subgrid at 450 m horizontal resolution, are not represented by the turbulence scheme. These results are in a good agreement with those obtained by Verrelle et al (2017) and Strauss et al (2019), who have shown that a commonly used eddy-diffusivity turbulence scheme underestimates the TKE at kilometric and hectometric (500 m) horizontal resolution, especially at the cloud edges but also in the updraught cores where the thermal production is misrepresented as the scheme does not enable the countergradient structures present in the updraught to be reproduced.…”
Section: Very Fine-scale Convective Organizationsupporting
confidence: 91%
“…The eddies near the cloud edges, which are subgrid at 450 m horizontal resolution, are not represented by the turbulence scheme. These results are in a good agreement with those obtained by Verrelle et al (2017) and Strauss et al (2019), who have shown that a commonly used eddy-diffusivity turbulence scheme underestimates the TKE at kilometric and hectometric (500 m) horizontal resolution, especially at the cloud edges but also in the updraught cores where the thermal production is misrepresented as the scheme does not enable the countergradient structures present in the updraught to be reproduced.…”
Section: Very Fine-scale Convective Organizationsupporting
confidence: 91%
“…The decision of taking a threshold of 1m s −1 for updraft and downdraft is motivated by the fact that we have to take into account the measurement uncertainty (less than 0.25-0.5m s −1 ). Additionally, we know that the variance of vertical turbulence is about 1.5 m 2 s −2 (taken from large eddy simulations at 50 m resolution; Verrelle et al, 2017;Strauss et al, 2019). The fact that median w ret for the merged dataset in MCS reflectivity zones 2 to 6 is smaller than 1 m s −1 confirms our decision to use a threshold of 1 m s −1 .…”
Section: Retrieved Vertical Velocity In Mcs Reflectivity Zonesmentioning
confidence: 73%
“…Between the four MCS locations, differences of aerosol loads and available ice nuclei might exist. Despite these possible differences, ice crystal formation mechanisms may be primarily controlled by dynamics, thermodynamics, and (particularly) secondary ice production rather than the pri- mary nucleation (Field et al, 2016;Phillips et al, 2018;Yano and Phillips, 2011) that regulates the concentrations of hydrometeors beyond ∼ 55 µm, making these concentrations rather similar for different MCS locations.…”
Section: Concentration Of Ice Hydrometeorsmentioning
confidence: 99%
“…At each interaction with the medium, the contribution of the direct Sun, transmitted along the tracked path, is added to the path weight, as per the local estimate method in a backward version. (b) Image of a high‐resolution congestus cloud (Strauss et al, ) over a complex ground rendered with 4,096 paths computed for each of the three spectral components of each of the 1,280 × 720 pixels (11,324,620,800 paths in total). The camera and Sun setup is described in Table in Appendix .…”
Section: Implementation and Performance Testsmentioning
confidence: 99%
“…Such rendering algorithms are also useful for evaluating the inversion procedures used to retrieve cloud parameters from satellite images. (Strauss et al, 2019) over a complex ground rendered with 4,096 paths computed for each of the three spectral components of each of the 1,280 × 720 pixels (11,324,620,800 paths in total). The camera and Sun setup is described in Table B1 in Appendix B.…”
Section: The Algorithmmentioning
confidence: 99%